The variation in post-endoscopy upper gastrointestinal cancer rates among endoscopy providers in England and associated factors: a population-based study - Kamran, Umair; Evison, Felicity; Morris, Eva Judith Ann; Brookes, Matthew J; Rutter, Matthew David; McCord, Mimi; Adderley, Nicola J; Trudgill, Nigel (Endoscopy, 2024)
Background Post-endoscopy upper gastrointestinal cancer (PEUGIC) is an important key performance indicator for endoscopy quality. We examined variation in PEUGIC rates among endoscopy providers in England and explored associated factors. Methods The was a population-based, retrospective, case–control study, examining data from National Cancer Registration and Analysis Service and Hospital Episode Statistics databases for esophageal and gastric cancers diagnosed between 2009 and 2018 in England. PEUGIC were cancers diagnosed 6 to 36 months after an endoscopy that did not diagnose cancer. Associated factors were identified using multivariable logistic regression analyses.Results The national PEUGIC rate was 8.5%, varying from 5% to 13% among endoscopy providers. Factors associated with PEUGIC included: female sex (odds ratio [OR] 1.29 [95%CI 1.23–1.36]); younger age (age >80 years, OR 0.52 [0.48–0.56], compared with ≤60 years); increasing comorbidity (Charlson score >4, OR 5.06 [4.45–5.76]); history of esophageal ulcer (OR 3.30 [3.11–3.50]), Barrett’s esophagus (OR 3.21 [3.02–3.42]), esophageal stricture (OR 1.28 [1.20–1.37]), or gastric ulcer (OR 1.55 [1.44–1.66]); squamous cell carcinoma (OR 1.50 [1.39–1.61]); and UK national endoscopy accreditation status – providers requiring improvement (OR 1.10 [1.01–1.20]), providers never assessed (OR 1.24 [1.04–1.47]).Conclusion PEUGIC rates varied threefold among endoscopy providers, suggesting unwarranted differences in endoscopy quality. PEUGIC was associated with endoscopy findings known to be associated with upper gastrointestinal cancer and a lack of national endoscopy provider accreditation. PEUGIC variations suggest an opportunity to raise performance standards to detect upper gastrointestinal cancers earlier and improve outcomes.